2019
DOI: 10.1002/anie.201907164
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Catalytic [2,3] Stevens and Sommelet–Hauser Rearrangements of α‐Diazo Pyrazoleamides with Sulfides

Abstract: Catalytic enantioselective [2,3] Stevens and Sommelet-Hauser rearrangements of a-diazo pyrazoleamides with sulfides were achieved by utilizing chiral N,N'-dioxide/nickel-( II )c omplex catalysts.T hese rearrangements proceeded well under mild reaction conditions,p roviding rapid and facile access to aseries of functionalized1,6-dicarbonyls or sulfanesubstituted phenylacetates with high to excellent enantioselectivities.T he catalytic system shows excellent stereocontrol, discriminating between the heterotopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 59 publications
0
31
0
1
Order By: Relevance
“…According to our previous work, [10a] the absolute configuration of the major products, [12,16] control experiments,a nd deuterium-labelling experiments,a sw ell as the general mechanism of [2,3] sigmatropic rearrangements, [18] the catalytic models for the enantiocontrol in the [2,3] Stevens and Sommelet-Hauser rearrangements are proposed ( Figure 1). When 1a is mixed with the chiral nickel(II) complex catalyst (Figure 1b,t op), decomposition by loss of nitrogen proceeds readily to form chiral nickel carbene intermediate A1.T he (phenylthio)acetate prefers to attack from the Re-face of nickel carbene because the Si-face is blocked by the left amide unit of the ligand (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to our previous work, [10a] the absolute configuration of the major products, [12,16] control experiments,a nd deuterium-labelling experiments,a sw ell as the general mechanism of [2,3] sigmatropic rearrangements, [18] the catalytic models for the enantiocontrol in the [2,3] Stevens and Sommelet-Hauser rearrangements are proposed ( Figure 1). When 1a is mixed with the chiral nickel(II) complex catalyst (Figure 1b,t op), decomposition by loss of nitrogen proceeds readily to form chiral nickel carbene intermediate A1.T he (phenylthio)acetate prefers to attack from the Re-face of nickel carbene because the Si-face is blocked by the left amide unit of the ligand (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Thed iazo compounds bearing a2naphthyl group and heterocyclic rings,also performed well to yield the corresponding products (3g-j)inexcellent enantioand diastereoselectivities (entries 7-10). Subsequently,t he scope with respect to the phenylthioacetate derivatives 2 was also examined ( Table 2, entries [11][12][13][14][15][16][17]. Furthermore,i faZ/E mixture of 1a was used for the reaction, it was found that am ajority of (Z)-1a was recovered, and the E isomer was consumed, yielding 3a in 46 %yield, 84:16 d.r.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations